Perlindungan Hukum Konsumen terhadap Pengalihan Uang Sisa Kembalian Ditinjau dari Hukum Islam (Studi Kasus Pada Indomaret Wijaya Kusuma 2 Kota Bekasi) - Ismi Hayatunnisa; Irvan Iswandi (Journal on Education, 2023)
The purpose of this study is to find out how the form of transfer of the remaining change in the sale and purchase transaction at Indomaret Wijaya Kusuma 2 and to find out how the consumer's legal protection against the transfer of the remaining change in terms of Islamic law in Indomaret Wijaya Kusuma 2. This research is a type of field research with a qualitative descriptive approach that describes a situation in society, and uses data collection methods, namely observation, interviews and documentation. The use of data sources is to use primary data and secondary data. Primary data were obtained through direct interviews with manager, cashier and consumers of Indomaret Wijaya Kusuma 2 Bekasi City, while secondary data were obtained through books, journals or other library materials related to the object of research. The results showed that the form of transfer of the remaining change at Indomaret Wijaya Kusuma 2 was donations. According to UUPK Number 8 of 1999, the transfer of the remaining change made by the cashier of Indomaret Wijaya Kusuma 2 which with the knowledge of the consumer is legal, because the consumer in this case has been notified by the cashier from the start if there is no availability of small money, then it is classified as non-existent. coercion because consumers are asked for their sincerity or approval of what is done by the cashier as a business actor so that the money is given voluntarily and not a unilateral action carried out by business actors. Meanwhile, viewed from Islamic law, the practice of diverting the remaining change in the form of donations at Indomaret Wijaya Kusuma 2 Bekasi City can be said to be legal, because the cashier and the consumer mutually accept this.